2016
DOI: 10.1097/jnr.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of an In-Service Education Program Designed to Enhance the Effectiveness of Physical Restraints

Abstract: In-service education for physical restraints enhances relevant knowledge and techniques but does not significantly affect attitudes or behaviors. Correct implementation of physical restraints not only promotes the quality of nursing care for patients in the ICU but also reduces the risk of physical-restraint-related complications. This study highlights the importance of changing the thoughts and concepts related to the use of physical restraints within the overall caring strategy of hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…However, in-service education alone had shown a low effect on attitudes and practices. 17,18 Thus, besides the clear need for in-service training, further research is needed to analyse other factors that could underpin belief and attitude formation such as fear, professional identity and feelings of nurse empowerment. Considering these circumstances, it is worth examining two core aspects: (1) why do organisations not share the responsibility of reducing physical restraint use in the ICU, inasmuch as this practice implies a risk for patients?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in-service education alone had shown a low effect on attitudes and practices. 17,18 Thus, besides the clear need for in-service training, further research is needed to analyse other factors that could underpin belief and attitude formation such as fear, professional identity and feelings of nurse empowerment. Considering these circumstances, it is worth examining two core aspects: (1) why do organisations not share the responsibility of reducing physical restraint use in the ICU, inasmuch as this practice implies a risk for patients?…”
Section: Discussionmentioning
confidence: 99%
“…However, these approaches showed a low impact on nurses' attitudes and practices, and their long-term effectiveness remains unexplored. 17,18 In their decision-making process, ICU nurses used intuition and heuristics instead of incorporating research evidence into daily practice. 19 Moreover, they have to carefully balance their decisions in a work environment that, frequently, exposed them to experienced ethical conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…Measures against preventable risk factors can be taken to prevent the occurrence of delirium effectively. Physical restraint is a preventable environment factor in delirium (Van Rompaey et al., ), which can be used either alone or in combination with chemical restraint to ensure patient safety, handle agitation and prevent unplanned extubation (Chang, Yu, Loh, & Chang, ; Hevener, Rickabaugh, & Marsh, ; Kandeel & Attia, ). The extent of physical restraint varies widely across countries, which has been reported to range from 0% to 100% (Benbenbishty, Adam, & Endacott, ; Martin & Mathisen, ; van der Kooi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…group. 27,28 In terms of the number of participants, all but three studies provided relevant information. The range of participants in each study with a total who received interventions are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%